2004
DOI: 10.1016/j.jtcvs.2002.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic laryngotracheal stenosis: Effective definitive treatment with laryngotracheal resection

Abstract: Idiopathic laryngotracheal stenosis is an entity that occurs almost exclusively in women and is without a known cause. It is not a progressive process, but the timing of the operation is crucial. Single-staged laryngotracheal resection is successful in restoring the airway while preserving voice quality in more than 90% of patients. Protective tracheostomy is now rarely required (1/30). Long-term follow-up shows a stable airway and improvement in voice quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 16 publications
2
148
0
5
Order By: Relevance
“…Major series of laryngotracheal resections published in literature [3][4][5][6][7][8][9][10][11] report good results rates ranging between 87% and 100%, and almost no mortality (generally under 1%), thus affirming the role of surgery as the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Major series of laryngotracheal resections published in literature [3][4][5][6][7][8][9][10][11] report good results rates ranging between 87% and 100%, and almost no mortality (generally under 1%), thus affirming the role of surgery as the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Marcillo et al [3] reported a 97% success rate with surgical correction in a study consisting of 64 cases with diagnoses of ISS. Endoscopic treatments are reported as good for palliation and as progressing with frequent recurrences in the long run [7]. There are also authors, most of which report achieving sufficient results with endoscopic treatment [8].…”
Section: Discussionmentioning
confidence: 99%
“…The major series of laryngo-tracheal resection published in the international literature report a high rate of good or excellent results, with low mortality (generally under 1-2%), supporting the role of surgery as the treatment of choice [10,[12][13][14][15][16][17].…”
Section: Subglottic Resectionsmentioning
confidence: 99%